2015
DOI: 10.1017/s0007114515004821
|View full text |Cite
|
Sign up to set email alerts
|

The acceptability of repeat Internet-based hybrid diet assessment of previous 24-h dietary intake: administration of the Oxford WebQ in UK Biobank

Abstract: Although dietary intake over a single 24-h period may be atypical of an individual's habitual pattern, multiple 24-h dietary assessments can be representative of habitual intake and help in assessing seasonal variation. Web-based questionnaires are convenient for the participant and result in automatic data capture for study investigators. This study reports on the acceptability of repeated web-based administration of the Oxford WebQ -a 24-h recall of frequency from a set food list suitable for self-completion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(112 citation statements)
references
References 22 publications
5
94
0
Order By: Relevance
“…Accumulating evidence has suggested that the effect of FTO on beverage choice might depend Diet data collection and phenotype definitions: Dietary intake was collected using a 24-hour recall questionnaire (Oxford WebQ) in a subset of UK Biobank participants (48). We used the mean intake from participants who completed at least two dietary recalls.…”
Section: Snp-heritability Estimates (H Gmentioning
confidence: 99%
“…Accumulating evidence has suggested that the effect of FTO on beverage choice might depend Diet data collection and phenotype definitions: Dietary intake was collected using a 24-hour recall questionnaire (Oxford WebQ) in a subset of UK Biobank participants (48). We used the mean intake from participants who completed at least two dietary recalls.…”
Section: Snp-heritability Estimates (H Gmentioning
confidence: 99%
“…The grouping of active and inactive individuals was estimated using the median value for the UK Biobank cohort equivalent to > 24.0 milligravity/d. Dietary information was collected via a self-reported dietary frequency questionnaire (Oxford WebQ; University of Oxford Cancer Epidemiology Unit, Oxford, UK), with questions about usual consumption of a range of foods (28). Participants were invited to complete the online questionnaire on five occasions between April 2009 and June 2012.…”
Section: Methodsmentioning
confidence: 99%
“…For participants who completed more than one online dietary questionnaire, mean values were calculated from all of the information provided, with variation between repeated measurement ranging from 26-34%, as described elsewhere (16). The intake of other food items such as red meat, processed meat, oily fish and fruit and vegetable were collected using a touchscreen questionnaire on the reported frequency of intake of these food items.…”
Section: Study Proceduresmentioning
confidence: 99%